KEMITRAAN ANTARA SINAR MAS LAND, PEMERINTAH KOTA TANGERANG SELATAN, DAN PEDAGANG DALAM PENGELOLAAN PASAR MODERN BSD CITY - Sarah Golda Sabrina Sitanggang; Priyatno Harsasto (Journal of Politic and Government Studies, 2019)
Traditional markets are generally synonymous with a dirty atmosphere, therefore Sinar Mas Land initiated the idea of establishing a traditional market that was packaged in a modern and partnership-based manner involving the South Tangerang City Government, as well as market traders. This partnership that has been running since 2004 has made this market a pilot market prototype for traditional markets throughout Indonesia. Therefore, this study aims to find out the mechanism of division of tasks of each actor involved in the partnership, and efforts made in order to maintain the success of the partnership. The research method used is descriptive qualitative with data collection techniques in the form of observation and interviews. The results of this study indicate that the success of a partnership depends very much on the synergy that exists between the actors involved by understanding the differences of each. In this case, both Sinar Mas Land, the South Tangerang City Government, and traders are divided into different mechanisms of responsibility according to their resources. Sinar Mas Land focuses on the system of administration and provision of technicians; government in terms of waste transportation, lab testing and calibration; and the trader in their participation follows a routine training program. The success of partnerships will run similar when using collaborative styles in conflict management; each actor strengthens their capacity for decision making; increase the capacity for discussion between actors. Keywords: partnership, traditional market, prototype